Live Long and Prosper : Aging in East Asia and Pacific - World Bank (Washington, DC, 2015)
This book discusses the societal and public policy challenges and reform options for the East Asia and Pacific countries as they address aging. The book aims to strike a balance between optimism and pessimism over aging. On the one hand, the impacts of aging on growth, labor markets, and public spending need not represent the unavoidable catastrophe sometimes feared. On the other hand, minimizing the downside risks of aging and ensuring healthy and productive aging will require proactive public policy, political leadership, and new mindsets across society.